A Literature Review on Protozoa Infection (Genus Giardia Lamblia): Threat to Swimming Athlete’s hygiene - Wrahatnala, Billy (Journal of Unified Multidisciplinary Practice in Sports, Health, and Medicine, 2026)
Freshwater sports can expose participants to a variety of pathogens, including Giardia lamblia, which can cause significant health risks. Swimming athletes, who often train in public pools or open water, have a high risk of exposure to these parasites due to direct contact with water that may be contaminated. Purpose: presents a comprehensive literature review on Giardia lamblia infection in the human body and identify the risk, impact and recommendations for infection prevention for swimming athletes. Materials and Methods: We searched Google Scholar, PubMed, and Scopus using the keywords: 'Giardia duodenalis OR Giardia lamblia OR Giardia intestinalis OR intestinal protozoa OR giardiasis OR giardiasis in swimming athletes. Result: . Giardia Lamblia is the only intestinal flagellate pathogenic protozoan known to be a major cause of the worldwide parasitic gastrointestinal disease called giardiasis (diarrhea) in vertebrates. Giardia infection can impact the health of athletes, especially those with weakened immune systems. Common symptoms include diarrhoea, abdominal cramps/pain, abdominal, bloating, nausea, and vomiting and dehydration. Research emphasises the importance of hygiene awareness and health education to prevent infections in swimming pools. Conclusion: In summary, enhancing hygiene awareness and health education is vital for preventing infections in swimming pools and freshwater sports. Key strategies include monitoring water quality, maintaining sanitation, and promoting hand washing. Increased awareness and regular health checks are essential, along with broader screening for giardiasis in at-risk populations.